Nghiên cứu thành phần chất màu anthocyanin chiết từ quả dâu tằm Quảng Nam - Cường, Đào Hùng; Cúc, Huỳnh Thị Kim (Vietnam Journal of Chemistry, 2012)
The method to identify the composition of anthocyanin coloured compound extracted from mulberry fruits (morus alba) in Quang Nam province in mixed solvent ethanol/water (1/1, 1% HCl) by using liquid chromatography - mass spectrometry LCQ-Finigan was introduced. The mobile phase consists of water, methanol and acetonitril 1% acetic acid with the proportion 30:60:10, with a flow rate at 0.7 ml/min; mass range: 10 - 1000; scan wavelength 400 - 600 nm; combining with the analysis of segment changes based on chromatography. The obtained results shown that three peaks of three molecules ions, with the saving moments at 2.37; 3.02 and 3.10 min, identified with heavy weight at m/z = 306.8; 595.1 and  449.0 are chloride of pelagonidin, cyanidin-3-0-glucoside and cyanidin-3-0-p-coumarylglucoside, respectively.